2018
DOI: 10.1016/j.ihj.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement in India—Early experience, challenges, and outcomes from a single center

Abstract: BackgroundDespite the increasing popularity of transcatheter aortic valve replacement (TAVR), only about 10,000 TAVR cases have been performed in Asia to date. The procedure is still in a nascent stage in India with very few centers offering this state-of-art technique. Here, we present the early results of TAVR experience at our center.MethodsForty-nine patients with severe symptomatic aortic stenosis (AS) were referred to our center for TAVR from November 2015 to February 2018. Twenty-five patients underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
1
2
Order By: Relevance
“…This was in contrast to 13.9% observed from US TAVI registry 2 and corresponding Indian study with all cause mortality of 8%. 3 Present study showed stroke rate of 13% which was quite high compared to other major studies as data from TVT registry report stroke rate of 2.5% at 30 days and 4.1% at 1 year and zero case from the Indian study. 3 , 4 …”
contrasting
confidence: 44%
See 1 more Smart Citation
“…This was in contrast to 13.9% observed from US TAVI registry 2 and corresponding Indian study with all cause mortality of 8%. 3 Present study showed stroke rate of 13% which was quite high compared to other major studies as data from TVT registry report stroke rate of 2.5% at 30 days and 4.1% at 1 year and zero case from the Indian study. 3 , 4 …”
contrasting
confidence: 44%
“… 3 Present study showed stroke rate of 13% which was quite high compared to other major studies as data from TVT registry report stroke rate of 2.5% at 30 days and 4.1% at 1 year and zero case from the Indian study. 3 , 4 …”
contrasting
confidence: 44%
“…There was increase in number of TAVR done during this year as the number of operators, the centers performing TAVR increased along with availability of made in India TAVR valve at a lower cost compared to pre-existing valves. 12 We are expecting further increase in number of TAVR procedures in coming years with expanding indications for TAVR and increased longevity in Indians. The NIC –CSI should try to capture the real time data which is robust with enormous research potential.…”
Section: Discussionmentioning
confidence: 99%